An Assessment of Malaysian Monetary Policy During the Global Financial Crisis of 2008-09 - Elekdag, Selim (IMF Working Papers; Working Paper ;, 2012)
Malaysia was hit hard by the global financial crisis of 2008-09. Anticipating the downturn that would follow the episode of extreme financial turbulence, Bank Negara Malaysia (BNM) let the exchange rate depreciate as capital flowed out, and preemptively cut the policy rate by 150 basis points. Against this backdrop, this paper tries to quantify how much deeper the recession would have been without the BNM's monetary policy response. Taking the most intense year of the crisis as our baseline (2008:Q4-2009:Q3), counterfactual simulations indicate that rather the actual outcome of a -2.9 percent contraction, growth would have been -3.4 percent if the BNM had not implemented countercyclical and discretionary interest rate cuts. Furthermore, had a fixed exchange rate regime been in place, simulations indicate that output would have contracted by -5.5 percent over the same four-quarter period. In other words, exchange rate flexibility and the interest rate cuts implemented by the BNM helped substantially soften the impact of the global financial crisis on the Malaysian economy. These counterfactual experiments are based on a structural model estimated using Malaysian data.